Analisis Faktor-Faktor Pencegah Tawuran Pelajar di SMK 2 Mei Bandar Lampung - ciciria, deri (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2019)
Vocational high school (SMK) 2 Mei Bandar Lampung is a school which its student majority are male. Many students solved their problems with anger and violence. This research was conducted to find the factors for preventing student brawl at SMK 2 Mei Bandar Lampung. The study found that emotional intelligence, religious guidance, school environment, and peers are four effective factors that can prevent student brawl. Whereas family and community environmental factors do not play an effective role in preventing students' brawl. Peers are the most influential tool in preventing students' brawl with the highest percentage of up to 52.1%. This should be a concern for parents and related parties (such as teachers) to pay more attention to their children/students' peers.